ESTABLISHING A SCALE TO ASSESS THE FACTORS AFFECTING THE COMPETITIVENESS OF TOURIST DESTINATIONS, A CASE STUDY IN HOI AN CITY, QUANG NAM PROVINCE - My Dung, Le; Phu Thang, Nguyen; Thi Hong, Nguyen (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
The competitiveness index of tourist destinations is essential for attracting visitors and adequately addressing their needs. Given that competitiveness is influenced by numerous factors, it is essential to create a scale for assessing these factors. This study developed a scale to evaluate factors affecting competitiveness in Hoi An city, Quang Nam province, a notable tourist destination recognized for the World Cultural Heritage site of Hoi An ancient town. The research employed descriptive statistics, utilizing Mean and Standard Deviation to develop a scale comprising seven-factor categories and 64 rating criteria. The preliminary results indicate that visitors largely concur with most groupings of elements affecting Hoi An’s competitiveness; however, several issues related to infrastructure and connectivity require attention in the destination’s tourism development.